OPTIMIZING THE USE OF LEARNING EQUIPMENT TO IMPROVE EDUCATION AT MAN 2 TULUNGAGUNG - Muh Ibnu Sholeh; Siti Fatinnah binti Ab Rahman; Nur ‘Azah; Sokip; Asrop Syafi’i; Muhammad fathurr’ouf; Sahri (EDUSIANA: Jurnal Manajemen dan Pendidikan Islam, 2024)
This research aims to analyze the current use of learning equipment, identify possible obstacles, and propose strategies or recommendations to maximize the use of learning equipment so that education at MAN 2 Tulungagung can be more effective, relevant and of high quality. This research method uses qualitative methods. Data collection was carried out through interviews, observation and documentation. Data analysis through data collection, data reduction and drawing conclusions. The research results show that the majority of teachers still rely on textbooks, while limited internet access, lack of teacher training in technology, and availability of devices are obstacles. Recommendations include improving technology access and teacher training, as well as collaboration between teachers and students in the development of digital learning content. It is hoped that these steps will maximize the use of learning equipment, creating a more effective, relevant and quality learning environment in line with the demands of an increasingly digitalized era. Continuous evaluation will be carried out to measure the impact of changes in the practice of using learning equipment on the quality of education at MAN 2 Tulungagung Keywords: Optimizing, Management, Learning Equipment, Education REFERENCE Abdullah, R. (2017). Pembelajaran Dalam Perspektif Kreativitas Guru Dalam Pemanfaatan Media Pembelajaran. Lantanida Journal, 4(1), 35. https://doi.org/10.22373/lj.v4i1.1866 Afrianti, S., & Musril, H. A. (2020). Perancangan Media Pembelajaran TIK Menggunakan Aplikasi Autoplay Media Studio 8 di SMA Muhammadiyah Padang Panjang. Jurnal Informatika Upgris, 6(2). Alvendri, D., & Giatman, M. (2023). Transformasi Pendidikan Kejuruan: Mengintegrasikan Teknologi IoT ke dalam Kurikulum Masa Depan. Journal of Education Research, 4(2), 752-758. Ambarwati, D., Wibowo, U. B., Arsyiadanti, H., & Susanti, S. (2021). Studi Literatur: Peran Inovasi Pendidikan pada Pembelajaran Berbasis Teknologi Digital. Jurnal Inovasi Teknologi Pendidikan, 8(2). Andriani, T. (2016). Sistem pembelajaran berbasis teknologi informasi dan komunikasi. Sosial Budaya, 12(1), 117-126. Anwar, S. (2021). Evaluasi Pendidikan Menuju Insan Kamil Perspektif Filsafat Islam. Jurnal Pendidikan Nusantara, 1(1), 62–76. https://doi.org/10.55080/jpn.v1i1.7 Ceha, R., Prasetyaningsih, E., Bachtiar, I., & Nana S., A. (2016). Peningkatan Kemampuan Guru Dalam Pemanfaatan Teknologi Informasi Pada Kegiatan Pembelajaran. ETHOS (Jurnal Penelitian dan Pengabdian), 3(1), 131. https://doi.org/10.29313/ethos.v0i0.1693 Dwiqi, G. C. S., Sudatha, I. G. W., & Sukmana, A. I. W. I. Y. (2020). Pengembangan Multimedia Pembelajaran Interaktif Mata Pelajaran IPA Untuk Siswa SD Kelas V. Jurnal Edutech Undiksha, 8(2), 33. https://doi.org/10.23887/jeu.v8i2.28934 Esterberg, K. G. (2018). Qualitative Methode in Social Research. Boston: McGrawn Hill Companies. Etikan, I. (2016). Comparison Of Convenience Sampling And Purposive Sampling. American Journal of Theoretical and Applied Statistics, 5(1). https://doi.org/10.11648/j.ajtas.201605 01.11 Haryadi, R. (2021). Problematika Pembelajaran Daring Di Masa Pandemi Covid-19. 12. Hidayati, N. (2016). Konsep Integrasi Tripusat Pendidikan Terhadap Kemajuan Masyarakat. Edukasia : Jurnal Penelitian Pendidikan Islam, 11(1). https://doi.org/10.21043/edukasia.v11i1.811 Ifadah, L. (2019). Strategi Pembelajaran Pendidikan Agama Islam Dalam Menghadapi Tantangan Era Revolusi Industri 4.0. Al Ghazali, 2(2). Komariah, A., & Halimah, N. (2022). Ragam Pemanfaatan Buku Teks Sebagai Media Pembelajaran Bahasa Inggris Di Kota Bitung Sulawesi Utara. Jurnal Ilmiah Iqra’, 16(2), 180. https://doi.org/10.30984/jii.v16i2.2045 Lubis, P., & Nasution, M. I. P. (2023). Gerakan Literasi Sekolah: Tantangan Literasi Di Era Digital Dan Cara Mengatasinya. Jurnal Media Infotama, 19(2), 487-496. Masdar Limbong, Firmansyah, Fauzi Fahmi, & Rabiatul Khairiah. (2022). Sumber Belajar Berbasis Media Pembelajaran Interaktif di Sekolah: Learning Resources Based on Interactive Learning Media in School. Decode: Jurnal Pendidikan Teknologi Informasi, 2(1), 27–35. https://doi.org/10.51454/decode.v2i1.27 Maudiarti, S. (2018). Penerapan E-Learning Di Perguruan Tinggi. Perspektif Ilmu Pendidikan, 32(1), 51–66. https://doi.org/10.21009/PIP.321.7 Miasari, R. S., Indar, C., Pratiwi, P., Purwoto, P., Salsabila, U. H., Amalia, U., & Romli, S. (2022). Teknologi pendidikan sebagai jembatan reformasi pembelajaran di indonesia lebih maju. Jurnal Manajemen Pendidikan Al Hadi, 2(1), 53. https://doi.org/10.31602/jmpd.v2i1.6390 Muhammad, A. R. (2018). Pendidikan Islam di Era Digital: Sebuah Tantangan dan Harapan (hlm. 49). Pustaka Pelajar. Myori, D. E., Chaniago, K., Hidayat, R., Eliza, F., & Fadli, R. (2019). Peningkatan Kompetensi Guru dalam Penguasaan Teknologi Informasi dan Komunikasi melalui Pelatihan Pengembangan Media Pembelajaran Berbasis Android. JTEV (Jurnal Teknik Elektro dan Vokasional), 5(2), 102. https://doi.org/10.24036/jtev.v5i2.106832 Nasrulloh, I., & Ismail, A. (2018). Analisis kebutuhan pembelajaran berbasis ict. Jurnal petik, 3(1), 28. https://doi.org/10.31980/jpetik.v3i1.355 Nasution, W. N. (2017). Perencanaan Pembelajaran: Pengertian, Tujuan Dan Prosedur. Ittihad: Jurnal Pendidikan, 1(2), 185-195. Parlindungan, D. P., Mahardika, G. P., & Yulinar, D. (2020). Efektivitas Media Pembelajaran Berbasis Video Pembelajaran dalam Pembelajaran Jarak Jauh (PJJ) di SD Islam An-Nuriyah. In Prosiding Seminar Nasional Penelitian LPPM UMJ, 3(3). Permatasari, A., & Kurniawan, A. (2021). Inovasi Strategi Pendidikan dalam Pengembangan Kurikulum Satuan Pendidikan. JIRA: Jurnal Inovasi dan Riset Akademik, 2(9), 1374–1386. https://doi.org/10.47387/jira.v2i9.226 Putra, F. A., Alim, F. N., Suseno, M. T., Yudha, S. S. P., & Thohir, I. A. (2021). Dampak Perkembangan Teknologi Internet dalam Pembelajaran Jarak Jauh bagi Siswa pada Masa Pandemi Covid-19. Journal of Education and Technology, 1(2), 93-103. Rahmawati, J., Ramadhani, E. P., & Saputra, D. (2023). Pelatihan Pemanfaatan Quizizz bagi Guru SMA Negeri 8 Kota Jambi untuk Transformasi Pembelajaran Digital. Jurnal Pengabdian Kepada Masyarakat, 1(1). Riyani, Y. (2012). Faktor-faktor yang Mempengaruhi Prestasi Belajar Mahasiswa. Jurnal EKSOS, 8(1). Romrell, D., Kidder, L. C., & Wood, E. (2014). The SAMR Model as a Framework for Evaluating mLearning. Online Learning, 18(2). https://doi.org/10.24059/olj.v18i2.435 Rosenberg, J. M., & Koehler, M. J. (2015). Context and Technological Pedagogical Content Knowledge (TPACK): A Systematic Review. Journal of Research on Technology in Education, 47(3), 186–210. https://doi.org/10.1080/15391523.2015.1052663 Sabandi, A. (2013). Supervisi Pendidikan Untuk Pengembangan Profesionalitas Guru Berkelanjutan. Pedagogi: Jurnal Ilmu Pendidikan, 13(2), 1-9. Sartika, F., Desriwita, E., & Ritonga, M. (2020). Pemanfaatan media pembelajaran dalam meningkatkan motivasi dan hasil belajar PAI di sekolah dan madrasah. Humanika, 20(2), 115–128. https://doi.org/10.21831/hum.v20i2.32598 Sholeh, M. I. (2023a). Strategi Efektif dalam Manajemen Pendidikan untuk Meningkatkan Kualitas Pembelajaran. Tarbawi Ngabar: Jurnal of Education, 4(2), 139–164. https://doi.org/10.55380/tarbawi.v4i2.462 Sholeh, M. I. (2023b). Strategi Pengembangan Sumber Daya Manusia Di Lembaga Pendidikan Islam Indonesia. dealita : jurnal pendidikan dan sosial keagamaan, v 3 no 1, 91–116. Sugiyono. (2018). Metode Penelitian Kombinasi (Mixed Methods). CV Alfabeta. Sujana, I. W. C. (2019). Fungsi dan tujuan pendidikan indonesia. Adi Widya: Jurnal Pendidikan Dasar, 4(1), 29. https://doi.org/10.25078/aw.v4i1.927 Sunarso, N. H. (2015). Teknologi pendidikan (hlm. 92–97). Cipta Prima Nusantara. Supriadi, S. (2017). Pemanfaatan sumber belajar dalam proses pembelajaran. Lantanida Journal, 3(2), 127. https://doi.org/10.22373/lj.v3i2.1654 Ulviani, M., Tahir, S. R., & Budiman, A. (2023). Pembuatan media pembelajaran sastra indonesia berbasis ict di lab. School smp unismuh makassar. Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 13(2). Wahidin, U. (2017). Peran budaya organisasi pendidikan islam dalam menghadapi tantangan pembangunan masyarakat, negara dan bangsa. Edukasi Islami : Jurnal Pendidikan Islam, 2(04). https://doi.org/10.30868/ei.v2i04.39 Warsihna, J., Mutmainah, S., & Utari, I. (2015). E-Sabak (Tablet) Untuk Pembelajaran Di Indonesia. Jurnal Teknodik, 19(3), 293–304. https://doi.org/10.32550/teknodik.v19i3.171 Warsita, B. (2017). Peran dan tantangan profesi pengembang teknologi pembelajaran pada pembelajaran abad 2. Kwangsan: Jurnal Teknologi Pendidikan, 5(2), 77-90. Yani, A. (2023). Transformasi Teknologi Dalam Pembelajaran Di Era Revolusi Industri 4.0. Jurnal PenKoMi: Kajian Pendidikan dan Ekonomi, 6(2), 68-75. Yuniarti, F., Dewi, P., & Susanti, R. (2012). Pengembangan virtual laboratory sebagai media pembelajaran berbasis komputer pada materi pembiakan. Journal of Biology Education, 1(1). Zahwa, F. A., & Syafi’i, I. (2022). Pemilihan Pengembangan Media Pembelajaran Berbasis Teknologi Informasi. Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 19(01), 61–78. https://doi.org/10.25134/equi.v19i01.3963 Zakariyah, A., & Hamid, A. (2020). Kolaborasi Peran Orang Tua dan Guru dalam Pembelajaran Pendidikan Agama Islam Berbasis Online di Rumah. Intizar, 26(1), 17–26. https://doi.org/10.19109/intizar.v26i1.5892